CFAB: COMPREHENSIVE FUNCTIONAL ASSESSMENT BATTERY FOR OLDER MICE. (16th November 2018) - Graber, T; Fry, C; Marota, R; Rasmussen, B
Abstract: Sarcopenia and frailty are incurable age-related diseases, producing a downward trajectory of decreased ability to perform activities of daily living, increased incidence of falls, eventual loss of independence, and increased mortality rate. To study basic mechanisms and assess potential therapies for sarcopenia and frailty, we need to comprehensively evaluate physical ability in mice as they age. We hypothesized that older C57BL/6 male mice (24/25-month old, n=30) would have reduced function compared to adult mice (6/7-month old, n=30). We tested this hypothesis with grip test (strength), rotarod (overall motor function), inverted cling (strength/endurance), treadmill (endurance), and voluntary wheel running (activity rate). We then developed a composite scoring system (CFAB) by summing z-scores of the individual functional tests in relation to the mean and standard deviation of the adult control group. In subsets from both age groups we determined muscle contractile function. Older mice had lowered capacity in inverted cling (37%, p<0.001), grip test (20%, p=0.001), rotarod (29%, p<0.001), voluntary wheel running (72%, p<0.001), and treadmill (5%, trend at p=0.077). Additionally, maximum dorsiflexion torque (19%, p=0.003), and soleus (22%, p<0.001) and EDL (37%, p<0.001) peak force were lower in older mice. The composite scoring system determined that older mice had reduced physical ability overall (scores: Older -3.936 versus Adults -0.293, p<0.001); though the best performers (upper 25%) of the older group maintained function and were indistinguishable from the average adult (p=0.335). In conclusion, our composite test is a powerful, non-invasive, and repeatable system to measure functional aptitude in future preclinical aging research.